Simulasi Waduk Petani Untuk Melayani Air Baku PDAM Tirta Dharma Duri - Andrian Tamtama Syafutra; Siswanto Siswanto; Yohana Lilis Handayani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Raw water needs to satisfy the water needs of the PDAM Tirta Dharma spines are fixed and continuous, while the availability of water from the water source to the season is not permanent. During the dry season river debit was small while the during the rainy season the flow rates are large and overflow. If the availability of water in the dry season is enough to satisfy needs of the raw water so raw water sampling can be done directly from surface runoff. But during the dry season when the flow rate is less than the requirement to satisfy needs of water storage reservoirs need to be made during the rainy season. Simulations were carried out based on equilibrium systems (water balance) in the Reservoir Petani showed that reservoir can serve the needs of clean water by taking water Duri City 100 liters / second, 150 liters / second, and 200 liters / second. Keywords :  Reservoir, Water Requirement, Storage Capacity